Bioenergetic Evaluation of Site-specific Keloid and FKN Fibroblasts - Chalwa, Temwani (Division of Dermatology, 2022)
Excessive scarring due to fibrosis from aberrant wound healing can lead to conditions such as Keloids or Folliculitis Keloidalis Nuchae (FKN). These fibroproliferative growths pose therapeutic challenges due to their complex aetiology that has been linked to multiple genetic and environmental factors, with frequent reoccurrence following therapy. Owing to reports on an increase in ATP and Fibroblast Activation Protein-1α production in keloids, the aim of this study was to investigate whether the disease phenotypes were linked to bioenergetic changes at a cellular level in these two conditions. Patient-derived tissue biopsies were used for fibroblast cell culture models, in which cell analysis was carried out to assess phenotype and different parameters of bioenergetic cellular behaviour. In addition to FKN and the intra- and peri-lesional Keloid patient fibroblasts, normal skin and non-hypertrophic (normo-trophic) scar fibroblasts were used as negative controls. The results show statistically significant and variable growth dynamics with increased proliferation and migration in keloid fibroblasts, while FKN fibroblasts showed a statistically significant increase in proliferation but had a similar migration profile to controls. The results further show that there is a statistically significant metabolic switch towards aerobic glycolysis in the fibroblasts from the disease conditions. During functional measurement of mitochondrial parameters, an increase in oxidative phosphorylation was exhibited in the disease conditions indicating their mitochondria were still functional. An increase in basal glycolysis with a concomitant increase in the cellular maximum glycolytic capacity was also demonstrated. Furthermore, protein analysis showed an upregulation in the expression of Fibroblast Activation Protein-1α in fibroblasts from both disease conditions This study begins to give novel insight into the bioenergetics of normal scars and scarring conditions such as FKN and, adds to the knowledge on the heterogeneity of fibroblasts derived from specific lesional sites within Keloids. These findings suggest that Keloids and FKN have a switch to a metabolic phenotype of aerobic glycolysis. This increase in glycolytic flux potentially proposes glycolytic inhibitors as a mechanistic basis for the treatment of these conditions.